Light‐Emitting Diodes: Highly Efficient Spectrally Stable Red Perovskite Light‐Emitting Diodes (Adv. Mater. 20/2018). Issue 20 (14th May 2018) - Tian, Yu; Zhou, Chenkun; Worku, Michael; Wang, Xi; Ling, Yichuan; Gao, Hanwei; Zhou, Yan; Miao, Yu; Guan, Jingjiao; Ma, Biwu
Abstract : Perovskite light‐emitting diodes (LEDs) have emerged as new‐generation electroluminescent devices. By using quasi‐2D perovskite/PEO composite thin films as the light‐emitting layer, in article number1707093, Biwu Ma and co‐workers report highly efficient spectrally stable red perovskite LEDs with a state‐of‐the‐art maximum brightness of around 1400 cd m −2 and a peak external quantum efficiency exceeding 6.2%.